Seminar for Research in Art Education - Research Abstracts for the National Art Education Association Conference (New Orleans, Louisiana, March 19-23, 1997) - Seminar for Research in Art Education; Connors, Kathleen E.; Seminar for Research in Art Education ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1997)
These abstracts are of the research presentations of the National Art Education Convention of 1997. The New Orleans 1997 Seminar for Research in Art Education (SRAE) Abstracts includes the 61 accepted proposals and the 11 task force and meeting presentations. They reflect an ongoing wide range and expanding mass of interests both traditional and tangential to the field. The abstracts of the convention presentations are arranged in alphabetical order by affiliation and title of the session. (EH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Art; Art Education; Curriculum Research; Educational Practices; Educational Research; Collected Works, Proceedings